2017
DOI: 10.1016/j.cbpa.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Targeting intracellular protein–protein interactions with cell-permeable cyclic peptides

Abstract: Intracellular protein-protein interactions (PPIs) are challenging targets for conventional drug modalities, because small molecules generally do not bind to their large, flat binding sites with high affinity, whereas monoclonal antibodies cannot cross the cell membrane to reach the targets. Cyclic peptides in the 700–2000 molecular-weight range have the sufficient size and a balanced conformational flexibility/rigidity for binding to flat PPI interfaces with antibody-like affinity and specificity. Several powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 58 publications
0
109
0
1
Order By: Relevance
“…And secondly, using specific IMHBs to modulate the overall IMHB impact on potency and permeability is the most risky strategy. 41 N-methylation 16 and more recently Lipophilic Prodrug Charge…”
Section: Incorporating Imhb In Drug Designmentioning
confidence: 99%
See 1 more Smart Citation
“…And secondly, using specific IMHBs to modulate the overall IMHB impact on potency and permeability is the most risky strategy. 41 N-methylation 16 and more recently Lipophilic Prodrug Charge…”
Section: Incorporating Imhb In Drug Designmentioning
confidence: 99%
“…However, it was shown that the physicochemical properties (e.g., lipophilicity and charge) and flexibility of cyclic hexapeptides direct their membrane permeation mechanisms. [13][14][15] IMHB, which modulates conformation and thus molecular lipophilicity is, therefore, an accepted key factor impacting on the permeability of cyclic hexapeptides, 5,16 which can provide medicinal chemists with significant help by acting as an additional tool that facilitates their design efforts.…”
Section: Introductionmentioning
confidence: 99%
“…These peptomers were not previously screened for any bioactivity and may have a high intrinsic potential to disrupt protein-protein interactions (30), such as those critical for assembly of a large proteinaceous structure such as the T3SS. The compounds were screened for the ability to inhibit NF-B activation during Y. pseudotuberculosis Δyop6 infection of HEK293-GFP cells.…”
Section: Development and Use Of An Nf-b-gfp Stable Cell Line For Idenmentioning
confidence: 99%
“…Given the need to compete against high‐affinity PPIs, some PPI blockers are larger than traditional small‐molecule therapeutics. Such large molecules can have poor cell permeability . This issue was encountered for the small molecule MM401 (Scheme ), which disrupted the interaction between WDR5 (a scaffolding protein involved in histone regulation) and MLL1 (a histone methyl transferase that positively regulates transcription) .…”
Section: Targeting Obligatory Interactionsmentioning
confidence: 99%
“…Such large molecules can have poor cell permeability. [65] This issue was encountered for the small molecule MM401 (Scheme 1), which disrupted the interaction between WDR5 (a scaffolding protein involved in histone regulation) and MLL1 (a histonem ethyl transferase that positively regulates transcription). [66] The WDR5/MLL1 PPI drivesa cutel ymphoblastic leukemia (ALL) with am ixed linear leukemic gene ( Figure 5).…”
Section: Wdr5/mll1mentioning
confidence: 99%